Mastering malware analysis : the complete malware analyst's guide to combating malicious software, APT, cybercrime, and IoT attacks /: the complete malware analyst's guide to combating malicious software, APT, cybercrime, and IoT attacks. (2022) - Kleymenov, Alexey; Thabet, Amr
No abstract available